Inclusive Education Management for Children with Special Needs at Budi Mulia Dua Elementary School, Sleman Regency - Evi Fitriyani; Rosalina Br. Ginting; Qristin Violinda (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Inclusive education in Indonesia requires schools to accommodate children with special needs (ABK), yet implementation remains inconsistent, particularly in planning, service delivery, monitoring, and evaluation. Objective: This study aims to analyze the management of inclusive education for children with special needs [ABK]) at Budi Mulia Dua Elementary School, Sleman Regency, including planning, implementation, monitoring, and evaluation. Methods: This research used a descriptive qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, the head of special assistant teachers, special assistant teachers, a child psychologist, and the parents of ABK students. Results: The results show that inclusive education planning is carried out through initial assessments and the involvement of various parties to identify students’ needs. The implementation of inclusive education takes place in regular classrooms with mentoring support tailored to the level of children’s needs, the provision of dedicated spaces, and practical activities to improve students’ skills. Monitoring is conducted periodically through classroom observation, communication with parents, and collaboration with Jogja Medical Center. Evaluation is conducted to assess the effectiveness of services and to review possible changes in initial assessments based on children’s development during the learning process. Conclusion: This study concludes that the success of inclusive education is determined by systematic, collaborative, and sustainable service management. The findings offer practical implications for school administrators seeking to replicate adaptive inclusive management models, particularly through flexible mentoring arrangements, the provision of dedicated resource spaces, and multi-stakeholder collaboration in planning and evaluation.